2007
DOI: 10.3171/spi-07/08/243
|View full text |Cite
|
Sign up to set email alerts
|

Atlantoaxial subluxation–induced myelopathy in cleidocranial dysplasia

Abstract: ✓The authors describe the clinical course and treatment of a patient with cleidocranial dysplasia in whom spastic myelopathy developed due to atlantoaxial subluxation. This 27-year-old woman with cleidocranial dysplasia and a history of atlantoaxial subluxation presented with spastic myelopathy. Surgery was performed twice for cervical myelopathy and atlantoaxial subluxation, including laminectomy at the atlas and cervicooccipital fusion in which the Luque rod system was used, as well as C1–2 fusion vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…3 The sequelae of the bony posterior fossa abnormalities have been better characterized in older patients, including reports of Chiari I malformation and syringomyelia, 4-5 as well as atlantoaxial subluxation and subsequent myelopathy. 6 Patients with CCD generally do well in the neonatal period, although the report from Gardner et al, 3 as well as the patient presented here, suggests that they may be more susceptible to intracranial hemorrhage. This vulnerability likely relates to the relative lack of brain parenchyma protection due to the underdeveloped skull.…”
Section: Discussionmentioning
confidence: 46%
“…3 The sequelae of the bony posterior fossa abnormalities have been better characterized in older patients, including reports of Chiari I malformation and syringomyelia, 4-5 as well as atlantoaxial subluxation and subsequent myelopathy. 6 Patients with CCD generally do well in the neonatal period, although the report from Gardner et al, 3 as well as the patient presented here, suggests that they may be more susceptible to intracranial hemorrhage. This vulnerability likely relates to the relative lack of brain parenchyma protection due to the underdeveloped skull.…”
Section: Discussionmentioning
confidence: 46%
“…31 An important aspect of the diagnosis of CCD in adult patients is the possible secondary complications, such as coxa vara, infections in the auditory system, and difficulties in vaginal delivery, for which cesarean sections are required. 32,33 Kobayashi et al 34 reported a case of atlantoaxial subluxation-induced myelopathy spastic in a 27-year-old patient with a history of CCD; the treatment involved surgery with cervical laminectomy. Furthermore, Vakili and Jalali 35 reported a case of hypogonadotropic hypogonadism associated with CCD in an adolescent patient.…”
Section: Discussionmentioning
confidence: 99%
“…In their retrospective study of 13 patients with deformities associated with rare disorders, Soultanis et al performed posterior instrumentation and fusion on an 18-year-old male cleidocranial dysostosis patient with a rigid thoracic curve (85°) and spina bifida in the lower cervical and superior thoracic spine and reported that the patient was stable after seven years of follow-up [ 27 ]. Kobayashi et al [ 28 ] published the clinical course and treatment outcomes of a 27-year-old female patient with cleidocranial dysostosis and spastic myelopathy due to atlanto-axial subluxation. The patient was operated two times for cervical myelopathy and atlanto-axial subluxation and had undergone a laminectomy of the atlas and C1-C2 fusion via a transpharyngeal approach and cervico-occipital fusion using Luque rod systems.…”
Section: Discussionmentioning
confidence: 99%